Analisa Kadar HbA1c Darah Vena dengan Antikoagulan EDTA dan Heparin Menggunakan Metode Imunofluoresens - Bastian (ARTERI : Jurnal Ilmu Kesehatan, 2023)
An unhealthy lifestyle can lead to chronic diseases, one of which is diabetes such as smoking habits, excessive alcohol consumption and careless eating habits. Diabetes is a non-communicable disease caused by the pancreas not functioning properly to produce insulin normally. HbA1c is a glycated hemoglobin and a subfraction resulting from the binding of a different glucose molecule to the HbA molecule (hemoglobin in adults), which increases with the average blood sugar concentration. This study aims to look at the differences in HbA1c levels in venous blood with the EDTA and Heparin immunofluency methods. The type of research used is pure experiment. This research was conducted in the Clinical Pathology Laboratory (PK) IKesT Muhammadiyah Palembang with a total of 29 samples. The results of research that has been done on Examination of HbA1c Levels Using Venous Blood with EDTA Anticoagulant and Heparin Immunofluency Method can be concluded that the average HbA1C value in the EDTA Anticoagulant sample is 7.9%, while the average HbA1C value in the Heparin Anticoagulant sample is 7. 8%. The Wilcoxon test obtained a p value â‰¤0.050 with a value of 0.021. The conclusion of this study was that there were differences in HbA1C levels in the EDTA and Heparin anticoagulant samples. Examination of HbA1c levels should use EDTA and Heparin anticoagulants because there are no anticoagulant particles that can affect the results of the examination and can provide accurate results because getting the average value of HbA1c levels is not too far away